The Impact of Functional Dependency on Outcomes After Complex General and Vascular Surgery. Issue 3 (March 2015) - Scarborough, John E.; Bennett, Kyla M.; Englum, Brian R.; Pappas, Theodore N.; Lagoo-Deenadayalan, Sandhya A.
Abstract : Objective: To describe the outcomes of functionally dependent patients who undergo major general or vascular surgery and to determine the relationship between functional health status and early postoperative outcomes. Background: In contrast to frailty, functional health status is a relatively easy entity to define and to measure and therefore may be a more practical variable to assess in patients who are being considered for major surgery. To date, few studies have assessed the impact of functional health status on surgical outcomes. Methods: Patients undergoing 1 of 10 complex general or vascular operations were extracted from the 2005 to 2010 America College of Surgeons National Surgical Quality Improvement Program database. Propensity score techniques were used to match patients with and without preoperative functional dependency on known patient- and procedure-related factors. The postoperative outcomes of this matched cohort were then compared. Results: A total of 10, 246 functionally dependent surgical patients were included for analysis. These patients were more acutely and chronically ill than functionally independent patients, and they had higher rates of mortality and morbidity for each of the 10 procedures analyzed. Propensity-matching techniques resulted in the creation of a cohort of functionally independent and dependent patients who were well matched for known patient- and procedure-related variables. Dependent patients from the matched cohort had a 1.75-fold greater odds of postoperative death (95% confidence interval: 1.54–1.98, P < 0.0001) than functionally independent patients. Conclusions: Preoperative functional dependency is an independent risk factor for mortality after major operation. Functional health status should be routinely assessed in patients who are being considered for complex surgery. Abstract : Our study describes 30-day mortality and morbidity rates for 10, 246 functionally dependent patients undergoing 10 different general or vascular surgical procedures. In a cohort of functionally independent versus dependent surgical patients well matched for known patient- and procedure-related factors, functional health status maintained an independent association with early postoperative outcomes.